Meet the expert : Tim O'Reilly and David Heinemeier Hansson (O'Reilly Media, 2020)
"Join us for this special conversation between Tim O'Reilly, founder and CEO of O'Reilly Media, and David Heinemeier Hansson, creator of Ruby on Rails and co-founder and CTO at Basecamp. They cover some of the key themes from three of David's best-selling books--It Doesn't Have to Be Crazy at Work, REWORK, and REMOTE: Office Not Required--as they examine how remote work can lead to more innovation and personal satisfaction and discuss how to run a calm company by forgoing the lure of excessive growth and making your time count for more."--Resource description page